Use of energy-saving operational technological systems in automation processes - Yo'ldoshova Hilola Baxtiyor qizi (Peerian Journals Publishing, 2023)
In this article, I have developed an energy-saving operating system system that includes remote control of technological processes and we tried to use this system scheme to automate robotic processes with the help of central monitoring equipment installed in buildings. Automation in technological processes on behalf of operations, we will be able to provide extensive opportunities for remote working to automatically perform energy-saving operations. In addition, as another feature, the system requires only a local network to connect, and we can automate based on the specifications of the central monitoring equipment, which ensures automatic operation regardless of networks. By objects designed to save energy this system consists of the optimal operation of the heat source system, the adjustment of the temperature of the supply water, and also heat source equipment, room temperature adjustment and outside air intake volume adjustment options are also available. Currently, the process automation operations manager has the role of performing these energy-saving operations, however finding the optimal value for each of these operations is causing difficulties and problems. Operational management in the technical system, is also responsible for tasks outside of facility operations such as maintenance management, therefore, regularly changing the optimal settings can be a very complex technological process. This system uses robotic process automation technology, so it can do everything and we will have the ability to effectively manage energy saving operations that can be performed by the central technological monitoring equipment.
Keywords: Scheme of energy-saving technological system; automation of technological robotic processes; technological monitoring building management device